Atomic scale surface modification of TiO2 3D nano-arrays: plasma enhanced atomic layer deposition of NiO for photocatalysis. Issue 1 (13th November 2020) - Innocent, Jerome W. F.; Napari, Mari; Johnson, Andrew L.; Harris-Lee, Thom R.; Regue, Miriam; Sajavaara, Timo; MacManus-Driscoll, Judith L.; Marken, Frank; Alkhalil, Feras
Abstract : Here we report the development of a new scalable and transferable plasma assisted atomic layer deposition (PEALD) process for the production of uniform, conformal and pinhole free NiO with sub-nanometre control on a commercial ALD reactor. Abstract : Here we report the development of a new scalable and transferable plasma assisted atomic layer deposition (PEALD) process for the production of uniform, conformal and pinhole free NiO with sub-nanometre control on a commercial ALD reactor. In this work we use the readily available nickel precursor nickelocene in conjunction with O2 plasma as a co-reagent (100 W) over a temperature range of 75–325 °C. An optimised growth per cycle of 0.036 nm was obtained at 250 °C with uniform thickness and coverage on scale-up to and including an 6 inch Si wafer (with a 200 nm thermal SiO2 top layer). The bulk characteristics of the NiO thin films were comprehensively interrogated by PXRD, Raman spectroscopy, UV-vis spectroscopy and XPS. The new NiO process was subsequently used to fabricate a 3D nanostructured NiO/TiO2 /FTO heterojunction by depositing 20 nm of NiO onto pre-fashioned TiO2 nanorods at 250 °C for application in the photo-electrolysis of water in a photoelectrochemical cell (PEC). The NiO/TiO2 3D array was shown to possess a peak current of 0.38 mA cm −2 at 1.23 VRHE when stimulated with a one sun lamp.